Relativistic model for the nonmesonic weak decay of single-lambda hypernuclei - Fontoura, C. E. (2016)
Having in mind its future extension for theoretical investigations related to charmed nuclei, we develop a relativistic formalism for the nonmesonic weak decay (NMWD) of single-λ hypernuclei in the framework of the independentparticle shell model and with the dynamics represented by the (π, K) onemeson-exchange model. Numerical results for the one-nucleon-induced transition rates of 12 λC are presented and compared with those obtained in the analogous nonrelativistic calculation. There is satisfactory agreement between the two approaches, and the only noteworthy difference is that the ratio γn/γp is appreciably higher and closer to the experimental value in the relativistic calculation. The ability of describing existing data, including the most recent ones, on NMWD of λ-hypernuclei, warrants application of the formalism to evaluate similar decay processes in charmed nuclei.